Green remediation of high-lead contaminated soil by stabilization/solidification with insoluble humin: Long-term leaching and mechanical characteristics. (15th November 2021) - Ge, Shangqi; Jiang, Wenhao; Zheng, Lingwei; Xie, Xinyu; Pan, Yize
Abstract : High concentrations of lead in soil will greatly weaken the stabilization/solidification effect. Humin (HM) is expected to improve this process because it is a neutral, insoluble, porous and green material as well as an eco-friendly adsorbent extracted from natural peat soil. However, HM has not been studied with respect to the stabilization/solidification (S/S) characteristics of potentially toxic element (PTE)-contaminated soil due to its different extraction sources and methods, as well as complex properties. To study these effects, insoluble HM was extracted for treatment of high-lead contaminated soil by cement-based S/S. The experimental results show that HM has a strong adsorption capacity for lead with a maximum adsorption capacity of 200.2 mg kg −1 . The negative influence of a high content of lead on the compressive strength over a 0–90-day period is weakened after adding HM to the soil, wherein a competitive mechanism between HM and a high concentration of lead is proposed. The lead leaching concentration of stabilized soil is significantly decreased under different leaching methods from 0 to 60 days and then decreases slowly. The lead speciation results for the stabilized soil determined through the Tessier sequential extraction method show that HM promotes the gradual chemical transformation of lead from exchangeable and carbonate-bound fractions to a more stable state, with respective decreases of 27.5% and 15.1%. In addition, SEM-EDS images show that HM with a high porosity and specific surface area coexists well with cement, which promotes the stabilization of lead. In conclusion, HM contributes to decreasing the mobility and bioavailability of lead and achieving environmental remediation. Graphical abstract: Image 1 Highlights: · Innovative application of neutral and stable humin in cement-based S/S. · Humin has a competing mechanism that results in an increase in UCS results. · Humin facilitates the stabilization of active lead ions in different leaching environments. · Humin can decrease the mobility and bioavailability of lead in stabilized soil. · The application of eco-friendly material humin is cost-effective and produces low carbon emissions. Abstract : Abstract